Diversity, Bacterial Symbionts, and Antimicrobial Potential of Termite-Associated Fungi - Xu, Xiao; Shao, Mingwei; Yin, Caiping; Mao, Zhenchuan; Shi, Jingjing; Yu, Xinyuan; Wang, Ying; Sun, Feifei; Zhang, Yinglao (Frontiers in Microbiology, 2020)
The phylogenetic diversity of fungi isolated from the Odontotermes formosanus was investigated by dilution-plate method, combined with morphological characteristics and 5.8s rDNA sequencing. Thirty-nine fungi were isolated and purified from O. formosanus, which were belonging to 2 phyla, 4 classes (Sordariomycetes, Dothideomycetes, Eurotiomycetes, Agaricomycetes). Furthermore, 9 bacterial 16S rRNA sequences were obtained from total fungal genomic DNA. All bacterial symbionts were segmented into 4 genera: Bacillus, Methylobacterium, Paenibacillus and Trabulsiella. The antimicrobial activities of all endophytic fungi extracts were tested by using the filter paper method against Escherichia coli (ATCC 8739), Bacillus subtilis (ATCC 6633), Staphylococcus aureus (ATCC 6538) and Canidia albicans (ATCC 10231). The results exhibited that 25 extracts (64%) exhibited antibacterial activity against at least one of the tested bacterial strains. Furthermore, the secondary metabolites 1 (5-hydroxyramulosin (1a): biatriosporin M (1b) = 2:1) from the Pleosporales sp. BYCDW4 exhibited potent antimicrobial activities against E. coli. C. albicans, B. subtilis, S. aureus with the inhibition zone diameter (IZD) of 13.67, 14.33, 12.17, 11.33 mm, respectively, which were comparable to those of the positive control. 1-(2,5-dihydroxyphenyl)-3-hydroxybutan-1-one (2) from the Microdiplodia sp. BYCDW8 showed medium inhibitory activities against B. subtilis and S. aureus, with the IZD range of 8.32-9.13 mm. In conclusion, the study showed the diversity of insect symbionts could be expected to develop the resource of new species and antibiotics.